2007
DOI: 10.1021/ie070180m
|View full text |Cite
|
Sign up to set email alerts
|

Role of Third Phase in Intensification of Reaction Rates and Selectivity:  Phase-Transfer Catalyzed Synthesis of Benzyl Phenyl Ether

Abstract: In the current work, the merits of the creation of a third phase in a typical biphasic reaction have been illustrated. The advantages of liquid-liquid-liquid phase-transfer catalysis (L-L-L PTC) have been brought out over liquid-liquid phase-transfer catalysis (L-L PTC) by considering the etherification of phenol by benzyl chloride to benzyl phenyl ether. L-L-L PTC is a novel strategy for waste reduction and improving profitability, in which a catalyst-rich middle phase is formed between the other two phases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…(8) was used to update the concentration of all the droplets after each particulate event in the simulation. All previous studies on a variety of reactions involving L–L–L PTC have reported an enhancement in the conversion when the third liquid phase (catalyst phase) appears 1–17. This shows the catalyst‐rich phase around the drop, where the reaction occurs, plays an important role in the conversion; hence, the film thickness cannot be neglected.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(8) was used to update the concentration of all the droplets after each particulate event in the simulation. All previous studies on a variety of reactions involving L–L–L PTC have reported an enhancement in the conversion when the third liquid phase (catalyst phase) appears 1–17. This shows the catalyst‐rich phase around the drop, where the reaction occurs, plays an important role in the conversion; hence, the film thickness cannot be neglected.…”
Section: Resultsmentioning
confidence: 97%
“…Phase transfer catalysis (PTC) has been used in more than 800 processes, particularly as liquid–liquid (L–L) and solid–liquid (S–L) systems for the past 40 years. However, only recently the importance of liquid–liquid–liquid (L–L–L) PTC has been demonstrated as a powerful method vis‐à‐vis biphasic PTC in commercially relevant reactions 1–17. The translation of L–L PTC into L–L–L PTC renders several benefits.…”
Section: Introductionmentioning
confidence: 99%
“…18,[39][40][41] The initial reaction rate with different catalyst usages in this PTC system were compared. As shown in Fig.1, the initial 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 8 reaction rate dramatically increases with the catalyst usage varied from 0.0153 to 0.020 mol/L.…”
Section: Effect Of the Catalyst Usage On The Formation Of The Third Pmentioning
confidence: 99%
“…[1][2][3] Liquid-liquid PTC (LL-PTC) system, solid-liquid PTC system, third-liquid PTC (TLPTC) system and solid-liquid-liquid system was always adopted used to conduct HI-PTC reaction. [4][5][6][7][8][9][10] Among these PTC systems, TLPTC has been demonstrated as a powerful method against biphasic PTC in a number of commercially hydroxide-initiated reactions. The advantages of TLPTC include high reaction rate and selectivity, easy separation of the catalyst and the product, mild reaction conditions, and steady reuse of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Dreiphasensysteme sind in der Phasentransferkatalyse bereits bekannt, [7,8] wobei dort die dritte Phase in der Regel zufällig wegen der Unlöslichkeit des Phasentransferkatalysators in den verwendeten Lösungsmitteln erhalten wird. In unserer Studie werden selbstaggregierende Tensidsysteme [9] mit einstellbarem Phasenverhalten als Reaktionsmedium in einer Suzuki-Kupplung, der Synthese von 4'-Methyl-2-biphenylcarbonitril (Schema 1), einer wichtigen Zwischenstufe für die Herstellung von Sartanen, verwendet.…”
unclassified